Pilot-scale continuous synthesis of a vanadium-doped LiFePO4/C nanocomposite high-rate cathodes for lithium-ion batteries - Johnson,ID; Luebke,M; Wu,OY; Makwana,NM; Smales,GJ; Islam,HU; Dedigama,RY; Gruar,RI; Tighe,CJ; Scanlon,DO; Cora,F; Brett,DJL; et al. (Journal of Power Sources, 2016)
A high performance vanadium-doped LiFePO4 (LFP) electrode is synthesized using a continuous hydrothermal method at a production rate of 6 kg per day. The supercritical water reagent rapidly generates core/shell nanoparticles with a thin, continuous carbon coating on the surface of LFP, which aids electron transport dynamics across the particle surface. Vanadium dopant concentration has a profound effect on the performance of LFP, where the composition LiFe0.95V0.05PO4, achieves a specific discharge capacity which is among the highest in the comparable literature (119 mA h g−1 at a discharge rate of 1500 mA g−1). Additionally, a combination of X-ray absorption spectroscopy analysis and hybrid-exchange density functional theory, suggest that vanadium ions replace both phosphorous and iron in the structure, thereby facilitating Li+ diffusion due to Li+ vacancy generation and changes in the crystal structure.